Home away from home: international students' experiences during the COVID-19 pandemic and the role of US higher education - Zhang, Xiaoqiao; Hsu, Kelly C.; Fleming, Kirsten E.; Liu, Cindy H.; Hahm, Hyeouk Chris (Frontiers in Psychology, 2023)
This study focuses on the impact of the COVID-19 pandemic on international students' overall experiences. We interviewed 22 international students from 11 countries and 17 universities in the US who participated in a large longitudinal study that aims to understand the physical and emotional well-being of young adults during the COVID-19 pandemic. Guided by Bronfenbrenner's ecological model, the findings suggested that students were impacted by the COVID-19 pandemic through interpersonal, institutional, political, and personal levels. The results showed that the pandemic exacerbated existing stressors such as the lack of social support from family, various visa regulations, competitive and limited job opportunities, discrimination and xenophobia, particularly towards students from Asia, and the financial burdens. Additionally, the findings highlighted students' perceived loss of the "American dream" and the uneven return of investment due to the pandemic. The study reveals the importance of US higher education institutions in supporting international students during the pandemic, particularly in terms of their sense of belonging. Recommendations for institutions drawn from the findings are proposed to better support international students during times of COVID-19 and beyond.